Pinch Current and Soft X-Ray Yield Limitations by Numerical Experiments on Nitrogen Plasma Focus - Akel, M.; Al-Hawat, Sh.; Lee, S. (Springer US, 2010)
The modified version of the Lee model code RADPF5-15a is used to run numerical experiments with nitrogen gas, for optimizing the nitrogen soft X-ray yield on PF-SY1. The static inductance L0 of the capacitor bank is progressively reduced to assess the effect on pinch current Ipinch. The experiments confirm the Ipinch, limitation effect in plasma focus, where there is an optimum L0 below which although the peak total current, Ipeak, continues to increase progressively with progressively reduced inductance L0, the Ipinch and consequently the soft X-ray yield, Ysxr, of that plasma focus would not increase, but instead decreases. For the PF-SY1 with capacitance of 25 lF, the optimum L0 = 5 nH, at which Ipinch = 254 kA, Ysxr = 5 J; reducing L0 further increases neither Ipinch nor nitrogen Ysxr. The obtained results indicate that reducing the present L0 of the PF-SY1 device will increase the nitrogen soft X-ray yield.